2000
DOI: 10.1071/ea99132
|View full text |Cite
|
Sign up to set email alerts
|

Water-use efficiency on irrigated dairy farms in northern Victoria and southern New South Wales

Abstract: A survey of 170 randomly selected, irrigated, dairy farms in northern Victoria and 9 in southern New South Wales was conducted to examine and benchmark the key factors influencing water-use efficiency. Water-use efficiency was defined as the amount of milk (kg milk fat plus protein) produced from pasture per megalitre of water (irrigation plus effective rainfall). Information on water-use, milk production, supplementary feeding, farm size and type, pasture management, and irrigation layout and management was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 6 publications
1
19
1
Order By: Relevance
“…Water footprint of two beef stocker grazing treatment systems with respect to total (observed from grazing plus predicted from hay) liveweight gain based on three rainfall inputs with irrigation. amount of milk by the sum of irrigation and effective rainfall (Armstrong et al, 2000). Martin and Gilley (1993) and assumptions from Risinger and Carver (1987).…”
Section: Relevance To Sustainability Of Beef Productionmentioning
confidence: 99%
“…Water footprint of two beef stocker grazing treatment systems with respect to total (observed from grazing plus predicted from hay) liveweight gain based on three rainfall inputs with irrigation. amount of milk by the sum of irrigation and effective rainfall (Armstrong et al, 2000). Martin and Gilley (1993) and assumptions from Risinger and Carver (1987).…”
Section: Relevance To Sustainability Of Beef Productionmentioning
confidence: 99%
“…, 1995) and without (Stockdale and King, 1980; Holmes and Parker, 1992; Macdonald et al. , 2008), as well as on commercial farms (Armstrong et al. , 2000; Kellaway and Harrington, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of milk produced (measured in kg milk solids (MS)) from pasture per megalitre of water applied by irrigation plus effective rainfall [20] Water productivity WP kg DM/ha.mm or t DM/ML…”
Section: Deficit Irrigationmentioning
confidence: 99%
“…These factors impact farm management practices and determine irrigation strategies (such as when to use irrigation water), forage selection (what species to grow), and the grazing/management strategies applied to forages. A survey of irrigated dairy farms in the region conducted about 20 years ago [20] found that there was a large range of water use efficiencies (WUE) ( Table 1) between farms (25-115 kg milk fat plus protein/ML water). This suggested that there was scope for many farms to increase efficiency and productivity by modifying farm management practices depending on the input variables.…”
Section: Introductionmentioning
confidence: 99%